Damage to the Blood-Brain Barrier during Experimental Cerebral Malaria Results from Synergistic Effects of CD8(+) T Cells with Different Specificities - Poh, Chek Meng (Infect Immun, 2014)
CD8(+) T cells play a pathogenic role in the development of murine experimental cerebral malaria (ECM) induced by Plasmodium berghei ANKA (PbA) infection in C57BL/6 mice. Only a limited number of CD8(+) epitopes have been described. Here, we report the identification of a new epitope from the bergheilysin protein recognized by PbA-specific CD8(+) T cells. Induction and functionality of these specific CD8(+) T cells were investigated in parallel with previously reported epitopes, using new tools such as tetramers and reporter cell lines that were developed for this study. We demonstrate that CD8(+) T cells of diverse specificities induced during PbA infection share many characteristics. They express cytolytic markers (gamma interferon [IFN-γ], granzyme B) and chemokine receptors (CXCR3, CCR5) and damage the blood-brain barrier in vivo. Our earlier finding that brain microvessels in mice infected with PbA, but not with non-ECM-causing strains, cross-presented a shared epitope was generalizable to these additional epitopes. Suppressing the induction of specific CD8(+) T cells through tolerization with a high-dose peptide injection was unable to confer protection against ECM, suggesting that CD8(+) T cells of other specificities participate in this process. The tools that we developed can be used to further investigate the heterogeneity of CD8(+) T cell responses that are involved in ECM.